Studying the accuracy of orthophotos on the example of various terrain models in study areas in Hungary - Varga, Zsolt; Czédli, Herta (Acta Geographica Debrecina Landscape & Environment series, 2018)
Depending on the orientation data, the accuracy of the applied terrain models and the field content of the orthophotos data of different accuracy can be obtained in the course of analysing orthophotos. Considering the factors influencing accuracy, differences resulted by the application of different elevation models are studied in this paper in two study areas in Hungary. Primary aim of this study is to determine the magnitude of differences between the co-ordinates of reference points digitized from orthophotos and that of points measure.